Child Labor - Willis, Laurie, editor 651967; Gale Group (Online service) 651863 (Detroit, MI : Greenhaven Press, a part of Gale, Cengage Learning, 2012)
Explores the issues surrounding child abuse by placing opinions from a wide range of sources in a pro/con format. Features articles that express various perspectives on this topic.